Combining Both Acceptorless Dehydrogenation and Borrowing Hydrogen Mechanisms in One System as Described by DFT Calculations. Issue 7 (12th April 2022) - Cicolella, Alessandra; C. D'Alterio, Massimo; Duran, Josep; Simon, Sílvia; Talarico, Giovanni; Poater, Albert
Abstract: The mechanisms for the formation of N‐substituted hydrazones by coupling of alcohols and hydrazine, achieved by the sequential processes of acceptorless dehydrogenation and borrowing hydrogen, has been unveiled by density functional theory (DFT) calculations. The release of water and molecular hydrogen as subproducts, combined with the Mn‐PNN pincer based catalyst describe a green environment. Mechanistically, apart from describing a complex system of three coupled catalytic pathways, calculations describe the pivotal role of two intermediates, which participate in two catalytic pathways each one. Finally, predictive catalysis plays the role to push forward this reaction toward milder conditions, and thus in line with green chemistry standards. Abstract : The sustainable mechanism of the manganese catalyzed coupling of alcohols with hydrazine is unveiled by density functional theory. It is a combination of three coupled catalytic pathways, joining the borrowing hydrogen and acceptorless dehydrogenation, giving as a result N‐substituted hydrazones together with water and molecular hydrogen. By predictive catalysis the system evolves toward milder conditions.